Building energy index (BEI) of hospital buildings in Iraq: A case study - Gatea, Anwer Abdulhussein; Batcha, Mohd Faizal Mohideen (Prince of Songkla University, 2021)
Hospitals are generally made by a large complex with many buildings serving different functions. These buildings such as the patient registration area, wards, operation theatre, emergency and trauma department and pharmacy operate continuously for twenty-four hours daily throughout the year, hence consuming a large amount of energy. This paper presents a pioneering case study carried out at three hospitals in Iraq, designated as Hospital A, Hospital B and Hospital C to analyze their energy intensity by determining the building energy index (BEI). This study also identified the factors affecting energy usage in these hospitals. Detailed energy audits were carried out in these hospitals, followed by desktop analysis and comparison with BEI values from selected hospitals reported in the literature. It was found that the average electricity consumed annually for a period of three years (2016 to 2018) by Hospital A, B, and C were 19,280,900 kWh, 11,958,121 kWh and 4,275,760 kWh, respectively. It was also found that more than 60% of the energy consumed in all three hospitals were by the air conditioning systems hence becoming the significant energy user (SEU). The study thus proposes methods to reduce the energy consumption in these hospitals without reducing their level of comfort. It was also found that the outside ambient temperature was the main factor that affecting the energy consumption in the building. The study concludes that the BEI values attained for the hospitals in this case study ranged from 360 to 532 kWh/m2 /year, which are relatively high and hence signifies the energy efficiency measures to be implemented in these hospitals.